The Effect of Service Quality, Location, and Brand Image on Customer Decisions to Transact at Bank Mandiri KCP Jakarta Mal Pondok Indah (PIM 1) - Bohari, Akbar; Rachmawati, Ike Kusdyah; Handoko, Yunus (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The banking industry in Indonesia in 2024 experienced various significant developments. One of them is the digitalization of banking. People adapt and transact using digital-based platforms to make transactions without having to visit the bank. Bank Mandiri also continues to innovate and transform to follow the current trends, including launching Livin by Mandiri and Smart Branch. This has an impact on the decreasing number of customers who come to the branch to make transactions because they can transact easily through the Livin by Mandiri application. On the other hand, some customers still feel happy and comfortable transacting with the integrated services presented by the smart branch. Customers who come to the branch office also have a great opportunity to be offered various products so as to generate income for the branch. This study aims to analyze the effect of service quality, location and brand image on customer decisions to transact at Bank Mandiri KCP Jakarta Mal Pondok Indah (PIM 1). This study uses a quantitative approach. The population in this study were customers at Bank Mandiri KCP Jakarta Mal Pondok Indah (PIM 1). 100 customers were used as samples. The analysis method used is multiple linear regression with the help of the SPSS program. The results of the study indicate that service quality partially has a positive and significant effect on customer decisions, location partially has a positive and significant effect on customer decisions, brand image partially has a positive and significant effect on customer decisions, service quality, location, and brand image simultaneously affect customer decisions to transact at Bank Mandiri KCP Jakarta Mal Pondok Indah (PIM 1).